Tingkat Pengetahuan Perawatan Payudara Pada Ibu Post Partum - Ni Nyoman Hartati; Suratiah Sur (Jurnal Gema Keperawatan, 2013)
In this study aims to determine the level knowledge overview of the definition, purpose, benefits, breast care measures in post partum mothers at Dauh Puri health centers by using descriptive method. The research was conducted in May until June 2012 with a sample of 30 respondents in Consecutive Sampling via filling questionnaires. Overall, the results of this study showed 17 respondents (57%) knowledgeable is well, 13 respondents (43%) knowledgeable enough and no respondents who have less knowledge. Therefore, For Health Workers in the Dauh Puri health center is to further develop and provide information on post-partum mother care especially about the breast so that a better knowledge through the provision of counseling through leaflets. So, This study describes research the variables are expected to develop research on the factors that influence level of knowledge, especially about the breast care